Mass Spectrometric Identification of Cardiac Troponin T in Urine of Patients Suffering from Acute Myocardial Infarction. (15th October 2019) - Streng, Alexander S; van der Linden, Noreen; Kocken, Jordy M M; Bekers, Otto; Bouwman, Freek G; Mariman, Edwin C M; Meex, Steven J R; Wodzig, Will K W H; de Boer, Douwe
Abstract: Background: Because of its high cardiospecificity, cardiac troponin T (cTnT) is one of the first-choice biomarkers to diagnose acute myocardial infarction (AMI). cTnT is extensively fragmented in serum of patients suffering from AMI. However, it is currently unknown whether all cTnT is completely degraded in the body or whether some cTnT fragments can leave the body via urine. The aim of the present study is to develop a method for the detection of cTnT in urine and to examine whether cTnT is detectable in patient urine. Methods: Proteins in urine samples of 20 patients were precipitated using a cTnT-specific immunoprecipitation technique and a nonspecific acetonitrile protein precipitation. After in-solution digestion of the precipitated proteins, the resulting peptides were separated and analyzed using HPLC and mass spectrometry with a targeted selected ion monitoring assay with data-dependent tandem mass spectrometry (t-SIM/dd-MS2). Results: The t-SIM/dd-MS2 assay was validated using a synthetic peptide standard containing 10 specific cTnT peptides of interest and with purified human intact cTnT spiked in urine from healthy individuals. Using this assay, 6 different cTnT-specific peptides were identified in urine samples from 3 different patients, all suffering from AMI. Conclusions: We show here for the first time that cTnT can be present in the urine of AMI patients using a targeted LC-MS/MS assay. Whether the presence of cTnT in urine reflects a physiological or pathophysiological process still needs to be elucidated.